2011
DOI: 10.1038/ajg.2011.83
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling and Response Signatures Associated With Differential Responses to Infliximab Treatment in Ulcerative Colitis

Abstract: Analysis of mRNA expression in mucosal biopsies following infliximab treatment provided insight into the response to therapy and molecular mechanisms of non-response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 29 publications
5
91
2
Order By: Relevance
“…Although there are no data available whether IBD patients non-responding to IFX therapy are at an increased risk for colon cancer, an animal study indicated that IBD animals treated with IFX are protected from colon cancer [22][23][24][25][26][27][28][29]. Therefore, one may also speculate that patients having high Wnt5a gene expression may be subjected to IFX non-responsiveness and, also, are at a higher risk of cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Although there are no data available whether IBD patients non-responding to IFX therapy are at an increased risk for colon cancer, an animal study indicated that IBD animals treated with IFX are protected from colon cancer [22][23][24][25][26][27][28][29]. Therefore, one may also speculate that patients having high Wnt5a gene expression may be subjected to IFX non-responsiveness and, also, are at a higher risk of cancer.…”
Section: Discussionmentioning
confidence: 97%
“…21,23,26,27 The genes which demonstrated the largest alteration in expression were associated with epithelial integrity such as CLDN8 and Paneth cell metaplasia (DEFA5, DEFA6, and REG1). The majority of genes reported to be associated with UC in previous studies are attributable to chronic inflammation and leukocyte infiltration into the mucosal tissue such as the SAA1 (serum amyloid A1), chemokine (C-X-C motif) ligands (CXCL6, CXCL11, CXCL13), and the matrix metallopeptidases (MMP1, MMP3, MMP12).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] In the vast majority of these studies, the samples were obtained from chronically inflamed tissue such that transcriptomic differences observed have been dominated by the consequences of tissue damage and the presence of infiltrating inflammatory cells. 21,24,26,27 A recent meta-analysis of a number of these studies 23 identified the tight junction molecule, claudin 8 (CLDN8), to be the most underexpressed gene in the colon in individuals with IBD. CLDN8 is a "barrier" tight junction molecule located in the apical part of the paracellular junction, 30 and thought to play a role in preventing paracellular back leakage of sodium.…”
mentioning
confidence: 99%
“…In UC, Infliximab had a significant effect on gene expression profiles of treatment responders and the affected genes are related to inflammatory response, cell-mediated immune responses and cell-cell signalling; moreover, such gene expression changes differentiated patients responding to placebo and Infliximab [13]. In colorectal mucosa, the clinical outcome of an induction therapy with Infliximab is inversely associated with the pre-treatment TNF-a gene expression levels [14].…”
Section: Figurementioning
confidence: 98%